Utilization of Adolescent-Friendly Health Services and Associated Factors among Adolescents in Biratnagar: Mixed Method Study - Subedi, Sabitra; Yangden, Namita; Niraula, Achala; Khadgi, Deepika; Mandal, Punam Kumari (Journal of Biratnagar Nursing Campus, 2025)
Background: Adolescence, the transition between childhood and adulthood (ages 10–19), is a critical period for physical and mental well-being. Adolescent Sexual and Reproductive Health (ASRH) services provide essential support for health concerns. This study aimed to assess the utilization of Adolescent Friendly Health Services (AFHS) and associated factors among adolescents in Biratnagar.Methodology: A cross-sectional quantitative study supplemented by qualitative inquiry was conducted from March 15 to April 15, 2023. The quantitative data were collected from 255 grade 10 students at Satya Narayan Secondary School, Biratnagar, via a self-administered structured questionnaire. Qualitative data were gathered through focus group discussions and key informant interviews and analyzed thematically, whereas quantitative data were processed by using SPSS.Results: The mean age of the respondents was 15.71±1.02 years. Nearly one-third (29%) of the adolescents utilized AFHSs. Factors influencing utilization included embarrassment in seeking services and service hour feasibility. Adolescents who felt embarrassed were less likely to access services. The qualitative findings identified three key factors affecting utilization: health system-related issues, societal influences, and individual barriers.Conclusion: This study revealed that only a minority of adolescents used AFHSs, with embarrassment and inconvenient service hours being major barriers. Enhancing awareness through local government initiatives, school collaboration, and community involvement is essential.